Six Steps in Making an Insurance Claim - Regina Fegan; Michael T. Olexa (EDIS)
The six steps to making an insurance claim are: contact your insurance agent immediately, carefully document your losses, protect your property from further damage or theft, work with your adjustor, settle your claim, and repair your home. These steps will be discussed throughout this publication. This document, IFAS publication DH0431, was published June 1998, revised May 2003. It is part of The Disaster Handbook, a component of the Comprehensive Disaster Preparedness and Recovery Education Module.